Task Allocation In Team Projects: Findings from an Experimental Online System to Support Students - Whatley, Janice (Proceedings of the International Conference on Networked Learning, 2008)
As more business organisations use global teams for solving problems or systems development, it becomes important for students to have experience of tools to support global team working and develop team skills for global as well as face to face team working. In Higher Education the team project is one of the best ways to develop a number of skills, including team working and use of CMC tools. In addition, students are learning about team working at the same time as learning about the subject matter. There is a move from face to face tuition at universities towards online provision, and many students are working from home whenever possible. Any support provided for student team working needs to be flexible, to enable students to work at convenient times and places, and should promote understanding of issues of team working, both on campus, in the workplace and globally. Many researchers have identified maintenance roles and task roles, as interrelated roles necessary to achieve successful team working. Groupware was originally designed for dispersed teams of workers, rather than students, to support the task oriented roles of team working, and offers limited support for the maintenance roles, which tend to be problematical both for learners on campus and staff in the workplace. Also groupware may not provide adequate support to help students to recognise the issues relating to team working. Previous work suggested that one difficulty the student teams experience is deciding who should do which part of the project. Thus a software support system was designed and implemented to automate the process of allocating the project tasks to individual team members, in order to study the effect of this function upon the maintenance and task roles of team working. The resulting system works by asking each team member to select from a list of team tasks those tasks they are able to do and those they like doing. The system uses reasoning to suggest which team members could be allocated to carry out which tasks, and whether any training in specific tasks is indicated by low skill levels. The team can use these suggestions as a basis for negotiation of the final allocation of the tasks of the project to individuals. Teams of 10 to 15 undergraduate students, carrying out systems development projects, as part of business information systems and information technology programmes of study, took part in trials over three successive years of study, following an action research approach to the investigation. Questionnaires, interviews and focus groups were used to gain feedback from the student users of the system. The software system did help the team leaders to allocate tasks, taking into consideration individual team members’ preferences. The output from the system was used as the basis for discussion between the members, and was thought to be very useful when the team leaders did not know their team members from previous work. The knowledge base resulting from the system was useful to highlight skill shortages, requiring some training, and enable team members to be paired off to complete tasks. The teams could also mitigate project risk, by ensuring the most appropriate member was responsible for key tasks. Students felt more confident that other team members were capable of successfully performing allocated tasks, indicating some degree of trust emanating from the system outputs, even though the system relied upon individuals to provide honest input. A reluctance to try something new was noted from some students in the study, although they acknowledged the importance of team projects in providing opportunities to try out and learn new skills. Suggestions for improvements to the system ranged from linking the system to project planning tools, to providing information and guidance on what is required to carry out the different project tasks.